2008
DOI: 10.1128/jvi.00981-08
|View full text |Cite
|
Sign up to set email alerts
|

Retroviruses Human Immunodeficiency Virus and Murine Leukemia Virus Are Enriched in Phosphoinositides

Abstract: Retroviruses acquire a lipid envelope during budding from the membrane of their hosts. Therefore, the composition of this envelope can provide important information about the budding process and its location. Here, we present mass spectrometry analysis of the lipid content of human immunodeficiency virus type 1 (HIV-1) and murine leukemia virus (MLV). The results of this comprehensive survey found that the overall lipid content of these viruses mostly matched that of the plasma membrane, which was considerably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
370
5
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(409 citation statements)
references
References 65 publications
33
370
5
1
Order By: Relevance
“…Whereas previous studies have demonstrated that HIV-1 particles incorporate both α2-3 NeuNAc-linked GM1 and GM3 gangliosides (12,18), a recent report suggests that assembly of HIV-1 Gag occurs at GM1-deficient lipid rafts (23). Our results support this recent finding and demonstrate that although GM1 can mediate mDC capture when added exogenously to virions (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Whereas previous studies have demonstrated that HIV-1 particles incorporate both α2-3 NeuNAc-linked GM1 and GM3 gangliosides (12,18), a recent report suggests that assembly of HIV-1 Gag occurs at GM1-deficient lipid rafts (23). Our results support this recent finding and demonstrate that although GM1 can mediate mDC capture when added exogenously to virions (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Because depletion of α2-3-linked gangliosides from the virion results in particles that are deficient for mDC capture, we predicted that enrichment of the virion with α2-3-linked gangliosides would result in enhanced mDC capture. Our analyses focused on GM3 and GM1, because both α2-3-linked gangliosides were previously reported to populate lipid rafts (13) and HIV-1 particles (12,18). We used three independent strategies to test this hypothesis: exogenous addition of lipid, artificial liposomes, and ganglioside up-regulation during monocyte activation or differentiation into a macrophage.…”
Section: Enrichment Of α2-3-linked Gangliosides Results In Enhanced Hmentioning
confidence: 99%
See 1 more Smart Citation
“…This high membrane order can be related to two causes. First, as cholesterol concentration is more than 40% in plasma membranes (40,41), not only the ordered but also the disordered phase of GPMVs likely contains considerable amounts of cholesterol, increasing the packing in the membrane. In addition, both phases are above the order of the unseparated GPMVs at 20°C (Fig.…”
Section: Analysis Of Phase Separation In Plasma Membranesmentioning
confidence: 99%
“…Only binding and rearrangements of virion glycoproteins releases energy to overcome the requirements for the formation of the negative curvature essential for fusion (19)(20)(21)(22). Furthermore, outer leaflets of virion envelopes are commonly enriched in glycolipids with relatively large hydrophilic heads, such as gangliosides, which favor positive curvature (23,24).…”
mentioning
confidence: 99%